Моделирование рисков в торговле - Горстка, М.С.; Королев, О.Л. (Культура народов Причерноморья, 2014)
Моделирование рисков в торговле. В данной статье рассматриваются такие вопросы, как
виды рисков, классификация рисков по родам опасности, по сферам проявления, по возможности
предвиденья, по источникам возникновения, по размеру возможного ущерба. Также в статье
рассматривается такой вопрос как современные методы количественной оценки уровня риска, в
котором рассмотрены три группы методов, для оценки уровня риска. У даній статті розглядаються такі питання, як види ризиків, класифікація ризиків за
родами небезпеки, за сферами прояву, по можливості передбачення, за джерелами виникнення, за
розміром можливого збитку. Також у статті розглядається таке питання як сучасні методи кількісної
оцінки рівня ризику, в якому розглянуто три групи методів, для оцінки рівня ризику. This article discusses issues such as the types of risks, risk classification to leave the danger in the
spheres of manifestations, wherever possible foresight on the source, the size of the possible damage to the
complexity of the study, on the financial implications, the nature of manifestation in time, as far as possible
insurance frequency implementation. Each classification is painted in detail what are the risks and a detailed
description of each of them. The article also examines this question as modern methods of quantifying the level
of risk, which examined three groups of methods to assess the level of risk. In the first group - the statistical
(probabilistic) methods, the second group - expert methods and methodology for assessing the level of risk, and
the third group - the computational and analytical methods and techniques of assessing the level of risk. In each
group listed a variety of methods, their scope, whether methods provide reliable results and require special
techniques to assess the level of risk.